DESIGN OF A PROTOTYPE MOBILE PHONE FOR VISUAL IMPAIRED PEOPLE - Usman, U.; Abdulwahab, L. (FUDMA JOURNAL OF SCIENCES, 2023)
Available mobile phone devices in the market have failed to be easily accessible by people with visual challenge; efforts made to create special and accessible mobile phones for this class of people have not yielded much advantage especially to those of them that have no form of western education or could not understand communications in English language. Through interview and previous publications the research investigated the level of mobile phone usage among Hausa-speaking people with visual disabilities. Findings revealed low level of access to mobile phone for communications, and reasons ranging from complexity of usage to costly nature of specially made phones for their class; hence creating a digital divide to access and use of mobile phones among them. To alleviate the challenges for visual impaired, then researcher proposed a mobile phone prototype program, to pave way for bridging the digital divide between people that are visually challenged and those that are not. The prototype has been developed to speak to its users in guiding them during usage and the spoken words are customised in Hausa and Pidgin English languages which are believed to be among popular languages spoken in the West African countries and by the target population, especially those that do not have access to western form of education. The design was implemented using Microsoft Visual Studio 2010 in conjunction with Microsoft Access 2010. The developed system has undergone series of tests and appeared to be a stepping stone for bridging digital divide among this group of people.
Keywords: Visual Impairment, Mobile Phone, Hausa, Pidgin-English, Prototype, Digital divide